ANCIENT EGYPTIAN LITERATURE: THE OLD, MIDDLE AND NEW KINGDOMS - Mamadkulova, Kamila (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article is devoted to Ancient Egyptian literature: ancient, middle and new reigns. Ancient Egyptian literature includes a wide range of narrative and poetic forms, including inscriptions on tombs, steles, obelisks, and temples; myths, stories and legends, religious writings, philosophical works, wisdom literature, autobiographies, biographies, historical writings, poetry, hymns, personal essays, letters and court records.